Pengaruh Kepercayaan Diri dan Disposisi Berpikir Kritis Terhadap Kemampuan Pemecahan Masalah Ilmu Pengetahuan Alam Siswa SMP Negeri di Kabupaten Bogor - Sasmita, Iwan; Suryana, Andri; Pertiwi, Rina Hidayati (ALFARISI: Jurnal Pendidikan MIPA, 2026)
The ability to solve problems is one of the key skills of the 21st century that is vital for students to master, especially in the context of learning Natural Sciences. This study aims to examine the impact of two factors, namely self-confidence and critical thinking disposition, both together and separately, on students' ability to solve science problems in Public Junior High Schools in Bogor Regency. The methodology applied in this study is a correlational survey involving 80 students as a sample. The statistical analysis used to test the hypothesis in this study is multiple linear regression. The results of this research reveal that: 1) There is a significant influence between self-confidence and critical thinking disposition simultaneously on students' ability to solve science problems in Public Junior High Schools in Bogor Regency, which is indicated by the sig value = 0.000 < 0.05 and Fhit = 95.022. 2) There is a significant influence of self-confidence on students' ability to solve science problems in Public Junior High Schools in Bogor Regency, as evidenced by the sig value = 0.000 < 0.05 and tt = 4.153. 3) Critical thinking disposition also has a significant influence on students' ability to solve science problems in Public Junior High Schools in Bogor Regency, with the sig value = 0.000 < 0.05 and tt = 4.440 as evidence. These findings emphasize the importance of increasing students' self-confidence and critical thinking disposition in the science learning process.
Keywords: Self-confidence; critical thinking disposition; science problem-solving abilities